2020
DOI: 10.1016/j.jcta.2019.105181
|View full text |Cite
|
Sign up to set email alerts
|

State transfer in strongly regular graphs with an edge perturbation

Abstract: Quantum walks, an important tool in quantum computing, have been very successfully investigated using techniques in algebraic graph theory. We are motivated by the study of state transfer in continuous-time quantum walks, which is understood to be a rare and interesting phenomenon. We consider a perturbation on an edge uv of a graph where we add a weight β to the edge and a loop of weight γ to each of u and v. We characterize when for this perturbation results in strongly cospectral vertices u and v. Applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In addition, G\a and G\b need not be isomorphic in order for a and b to be cospectral, it is only necessary for their adjacency matrices to have the same spectrum. It is known that in strongly regular graphs, any pair of vertices is cospectral [13], and most examples of strongly regular graphs have no automorphisms and will not have G\a isomorphic to G\b. In addition, graphs with cospectral pairs can be constructed from cospectral graphs involved in Godsil-McKay switching (see [15]).…”
Section: Cospectral and Strongly Cospectral Verticesmentioning
confidence: 99%
“…In addition, G\a and G\b need not be isomorphic in order for a and b to be cospectral, it is only necessary for their adjacency matrices to have the same spectrum. It is known that in strongly regular graphs, any pair of vertices is cospectral [13], and most examples of strongly regular graphs have no automorphisms and will not have G\a isomorphic to G\b. In addition, graphs with cospectral pairs can be constructed from cospectral graphs involved in Godsil-McKay switching (see [15]).…”
Section: Cospectral and Strongly Cospectral Verticesmentioning
confidence: 99%
“…Godsil, Guo, Kempton, and Lippner [17] considered the problem of achieving perfect and pretty good state transfer in strongly regular graphs. A graph G is strongly regular if it is neither empty nor complete, it is k-regular for some integer k, every pair of adjacent vertices has a common neighbours, and every pair of nonadjacent vertices has c common neighbours.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 1.5. [17] Let G be a strongly regular graph with eigenvalues k, θ, τ . Then if k ≡ θ ≡ τ (mod 4) is odd (resp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in [15] showed that in graphs with an involutional symmetry, one can often induce pretty good state transfer between a pair of nodes by appropriately choosing a potential on the vertex set. In [10], it is shown that a potential can induce pretty good state transfer in strongly regular graphs as well. The contribution of this paper is to show how to construct asymmetric, non-regular graphs that admit PGST between a pair of nodes u, v if a suitably chosen potential is added to the adjacency matrix at u and v. The novelty of our constructions is that we do not require any symmetry or regularity in the graph.…”
Section: Introductionmentioning
confidence: 99%